MEDU-02. ABL1 AND 2 PLAY A KEY ROLE IN MEDULLOBLASTOMA GROUP 3 AND 4 TUMOR PROLIFERATION AND LEPTOMENINGEAL DISSEMINATION. (23rd April 2019) - Thompson, Eric; Hassen, Wafa; Jones, Jill; Hoj, Jacob; Pendergast, Ann Marie
Abstract: INTRODUCTION: The molecular underpinnings and treatment of leptomeningeal medulloblastoma metastases are not well characterized. The Abelson (ABL) family kinases play an important role in lung cancer cell migration, invasion, cell adhesion, and chemotherapy resistance. c-Abl is a key upstream regulator in the expression of c-myc in fibroblasts. The objective of this work was to elucidate the role of ABL kinases in medulloblastoma leptomeningeal dissemination. METHODS: ABL1 and ABL2 mRNA expression from a 272 pediatric tumor patient cohort and from a 767 medulloblastoma-only patient cohort was analyzed. ABL 1 and 2 protein expression from 7 medulloblastoma cell lines was determine using Western blots. shRNA was used to create stable double knockdowns of ABL1/2. The selective ABL1/2 inhibitors, nilotinib and GNF5, were used to determine their effect on medulloblastoma proliferation. RESULTS: In a cohort of 14 pediatric tumors, ABL1 and ABL2 expression was significantly higher in Group 3 and Group 4 medulloblastoma compared to other tumor types (P<0.05). In medulloblastoma patients, ABL1 and ABL2 levels were significantly higher in M+ than M0 patients (P=2.5x10 -10 and 7.2x10 -7, respectively) and overall survival was significantly reduced in patients with high ABL1 and 2 expression (P=6.9x10 -3 and 7.8x10 -5, respectively). ABL1 and 2 protein expression was robust in all cell lines. Knockdown of ABL1/2 significantly decreased c-myc expression (P<0.05). Pharmacologic inhibition of ABL1 and ABL2 resulted in significantly decreased cellular proliferation at 48 hours in multiple medulloblastoma cell lines. CONCLUSIONS: ABL1 and ABL2 are preferentially expressed in Group 3 and 4 medulloblastoma, in patients with metastases at diagnosis, and are associated with poor survival. Genetic inactivation of ABL1 and 2 resulted in decreased c-myc expression and pharmacologic inhibition resulted in decreased proliferation. This preliminary work suggests a role for ABL1/2 in the promotion of medulloblastoma leptomeningeal metastases and warrants further in vitro and in vivo exploration.